KNOWLEDGE MANAGEMENT IN INTERNATIONAL COMPANIES: SPECIFIC FEATURES AND INFORMATION TOOLS - Polyakov, Maxim; Khanin, Igor; Shevchenko, Gennadii; Bilozubenko, Volodymyr (Fìnansovo-kreditna dìâlʹnìstʹ: problemi teorìì̈ ta praktiki (Online), 2023)
The increasing importance of innovation as a factor in the effectiveness and competitiveness of companies makes them pay special attention to the processes of obtaining and using knowledge that require special management. International companies, being innovatively active for expansion, are a special subject of knowledge management (KM). In such companies, KM has significant specific features related to their structure, which includes foreign subsidiaries, and the nature of their activities, covering different national markets. Due to the specifics of such companies, they widely use information technology in management and, in particular, use special information tools for KM.The research is aimed to characterize the specific features of KM in international companies and to provide the rationale behind using new information tools for KM, which can be used to improve the effectiveness of innovation.The main focus of the paper is on the specific features of KM in international companies, taking into account their structure and nature of activities, namely: 1) specific features related to the content of the KM, taking into account the number of subsidiaries, the scale of activities, the complexity of tasks, etc.; comparison of the models of internalization and externalization in obtaining new knowledge by companies; 2) specific features related to the internal environment (involvement of all levels of management, multicultural environment, creation of communities of intensive knowledge); 3) specific features related to the external environment, covering interaction with consumers, partners and authorities of different countries; 4) specific features related to the innovative activity (distribution of powers between the parent company and subsidiaries, coordination of research and development (R&D), organization of innovation processes). The global approach of international companies to the development of innovations is substantiated, which determines the content of KM, as well as the need to create a KM system, part of which is information tools. Their improvement allows for enhancing the quality of KM and the effectiveness of innovation. In terms of KM in an international company, the purpose of such information tools as an R&D management information system, a single innovation management platform, a tool for formalizing knowledge, and a corporate knowledge base, is determined. In the future, it is expected to study the effects of the proposed tools, highlight the problems of their introduction and operation, as well as a set of measures to overcome these problems.